Impact of new generation granular insecticides on beneficial fauna of paddy ecosystem - Niranjan H P (Department of Agricultural Entomology, College of Agriculture, 2018)
The research on “Impact of new generation granular insecticides on beneficial fauna of paddy ecosystem” was carried out at College of Agriculture, Vellayani during 2016-18 to study the effect of newly recommended granular insecticides on the non-target organisms viz., parasitoids, predators and soil fauna of paddy ecosystem at recommended and double the recommended doses. The field experiment was done at Integrated Farming System Research Station (IFSRS), Karamana. Soil and water samples were tested to estimate residues and the degradation studies of the granular insecticides were also conducted. A field experiment was conducted with the rice variety Uma. The treatments were chlorantraniliprole 0.4 G at 10 and 20 kg ha-1, fipronil 0.3 G at 10 and 20 kg ha-1 and cartap hydrochloride 4 G at 25 and 50 kg ha-1. Major pests viz., stem borer, leaf roller and rice bug were recorded during the study. Among natural enemies major predators like damselflies, dragonflies, ground beetles, coccinellids and spiders were recorded and parasitoids of the order hymenoptera were observed. Soil fauna like ground beetles, water scavenger, ants, snails, spiders, nematodes and earthworms were recorded. Results revealed that, among the new generation granular insecticides fipronil 0.3 G at both 10 kg ha-1 and 20 kg ha-1 was found to be effective and superior to other treatments in reducing the damage (2.33 and 2.79 per cent of dead hearts at 75 days and 5.63 and 4.07 per cent of white ear heads at 90 days after transplanting [DAT] respectively) and population of adult stem borer (0.67 and 0.33 at 75 DAT respectively). Leaf roller damage (2.00 and 1.85 per cent at 75 DAT respectively) and its population (0.00 and 0.00 at 75 DAT respectively) were reduced significantly with chlorantraniliprole 0.4 G at both recommended and double the recommended dose. Cartap hydrochloride 4 G at 25 kg ha-1 effectively reduced the rice bug population (10.63 and 6.33 at 75 and 90 DAT) among the recommended insecticides. Among the new generation granular insecticides fipronil 0.3 G at 20 kg ha-1 followed by the recommended dose of 10 kg ha -1 was found to be toxic to natural enemies (predators of 10.33 and 13.33 at 75 days and parasitoids of 1.34 and 1.67 at 75 DAT) and soil fauna at all stages of the crop. Chlorantraniliprole 0.4 G at recommended dose of 10 kg ha -1 (21.67 of predators and 2.00 of parasitoids at 75 DAT) followed by double the recommended dose of 20 kg ha -1 (19.67 of predators and 1.34 of parasitoids at 75 DAT) were found to be safe to natural enemies and soil fauna. The P: D ratio of chlorantraniliprole 0.4 G (10 and 20 kg ha-1) were 0.93 and 0.92 at 75 DAT respectively. Dissipation of residues of selected insecticides fipronil 0.3 G and chlorantraniliprole 0.4 G was studied by analyzing the soil and water samples collected at 0, 1, 3, 5, 7, 10, 15 and 30 days after treatment with insecticides at recommended and double the recommended doses. The results revealed that fipronil 0.3 G at both doses dissipated within two hours (0 day) after treatment in both soil and water. Residues of chlorantraniliprole 0.4 G at both doses dissipated within two hours after treatment in water and five days after treatment in soil. New generation insecticides fipronil 0.3 G (10 kg ha-1), chlorantraniliprole 0.4 G (10 kg ha-1) and cartap hydrochloride 4 G (25 kg ha-1) were found effective against stem borer, leaf roller and rice bugs respectively. The present study revealed that among all the tested insecticides chlorantraniliprole 0.4 G at 10 kg ha-1 was safe to natural enemies and soil fauna with a low P: D ratio along with suppression of the insect pests.